Developing a triple helix approach for CO2 utilisation assessment. (28th April 2021) - McCord, Stephen; Armstrong, Katy; Styring, Peter
Abstract : We propose a new screening-type social impact assessment for developing CDU technologies; the method can be used as a standalone assessment or integrated with TEA and LCA to create a holistic sustainability study to enhance effective decision making. Abstract : Assessment of the sustainability of CO2 utilisation technologies should encompass economic, environmental and social aspects. Though guidelines for economic and environmental assessment of CO2 utilisation (CDU) have been presented, a methodology for social assessment of CDU has not. Herewith, social impact assessment for CDU is systematically investigated, a methodological framework derived and examples of application given. Both process and deployment scenarios are found to be key factors in the assessment and the sourcing of raw material is observed to be a hotspot for social impacts within the assessed CDU technologies. This framework contributes a new aspect to the development of holistic sustainability assessment methodologies for CDU by enabling a triple helix to be created between life cycle assessment (LCA), techno-economic assessment (TEA) and social impact assessment (SIA). Therefore, the triple helix approach will enable trade-offs between environmental, economic and social impacts to be explored, ultimately enhancing effective decision making for CDU development and deployment.